Chapter 8 The Logics of Vulnerability Challenging the Ungrievable Différance of the Other in Tabish Khair's Just Another Jihadi Jane (2016) - Gámez Fernández, Cristina María (Taylor & Francis, 2023)
Tabish Khair's Just Another Jihadi Jane (2014) explores the global phenomenon of female suicide bombers after the emergence of Islamic State of Iraq and Syria and the international reconfiguration of geopolitical power after 9/11. Khair tells the story of Jamilla and Ameena, two British teenage girls of South Asian Muslim descent who decide to join Islamic State in their search for their religious ideal of Islamic truth and their impending need for belonging and recognition. This chapter analyzes the multi-dimensional complexity of vulnerability exposed both in the story thematization and in the narrative mode of fictional testimony (Ganteau 2015). Firstly, it describes the story emplotment vertebrated along two different axes: the socioeconomic and cultural context that articulates vulnerability as precarity (Butler 2004; 2009) and the conditions of the precariat (Standing 2011); and female vulnerability to oppression and patriarchal violence after the girls move to Syria. Secondly, this chapter investigates the materiality of the narrative medium of fictional testimony as a precarious yet creative vehicle to expose vulnerability. Ultimately, this chapter contends that Khair's story and narrative form particularize the stereotyped jihadi Jane, shattering to pieces the sociopolitical ungrievability imposed on their différance (Derrida 1968) and their wasted lives (Bauman 2004).